2013
DOI: 10.3390/antib2030517
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Receptor-Like Antibodies: Targeting the Intracellular Proteome Therapeutic Potential and Clinical Applications

Abstract: Major histocompatibility complex (MHC) class I molecules are key in the immune response against malignant cells by shaping the T-cell repertoire and presenting peptides from endogenous antigens to CD8+ cytotoxic T cells. Because of their unique specificity, MHC-peptide complexes are a desirable target for novel immunotherapeutic approaches. These complexes can be targeted by recombinant T-cell receptors (TCRs). However, most TCRs produced thus far have affinities which are too low for target detection under no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 90 publications
0
32
0
Order By: Relevance
“…They also bypass the patient-specific limitations of CTL-based therapies. Only a few TCRm have been studied in preclinical models as agents for cancer therapy (15,29,36,(52)(53)(54)(55). Therefore, the present study on Pr20 adds additional proof-of-concept that TCRm can be potent and selective therapeutic agents.…”
Section: Discussionmentioning
confidence: 78%
“…They also bypass the patient-specific limitations of CTL-based therapies. Only a few TCRm have been studied in preclinical models as agents for cancer therapy (15,29,36,(52)(53)(54)(55). Therefore, the present study on Pr20 adds additional proof-of-concept that TCRm can be potent and selective therapeutic agents.…”
Section: Discussionmentioning
confidence: 78%
“…Antibodies targeting disease-associated peptide–MHC-I complexes, the so-called TCRm antibodies or TCR-like antibodies, are similar to the TCR in that they bind both the peptide and the MHC-I molecule and, therefore, their binding is both peptide-specific and MHC-restricted ( 52 , 53 ). TCRm antibodies have expanded the range of targetable antigens to include intracellular proteins without the delivery complications associated with intracellular antibodies.…”
Section: T-cell Receptor Mimic (Tcrm) Antibodiesmentioning
confidence: 99%
“…TCRm antibodies have been produced either by immunization or by phage display, with both strategies presenting their respective pros and cons. One of the main limitations in the production of TCRm antibodies by both strategies was the correct refolding of recombinant peptide–MHC complexes and their purification ( 53 ). Recombinant peptide–MHC complexes are made by using bacterial expression to generate inclusion bodies containing the extracellular domains of the heavy chain of human leukocyte antigen (HLA) and β2-microglobulin.…”
Section: T-cell Receptor Mimic (Tcrm) Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As antibodies, TCR-like mAbs also exhibit better stabilities and higher affinities than TCRs. 9 Over the years, increasing interest in TCR-like mAbs has led to a rapid expansion of the repertoire of TCRlike mAbs targeting both viral [10][11][12][13] and tumor-associated antigens. [14][15][16][17][18][19] These studies have demonstrated the feasibility of TCR-like mAbs to target cells expressing neoantigen, independent of the immunoregulatory microenvironment that might inhibit T-cell function.…”
Section: Introductionmentioning
confidence: 99%